To solve the equation \( 20x - 5(6x + 15) = -45 \), we can follow these steps:
-
Distribute the \(-5\) in the expression \(-5(6x + 15)\): \[ -5(6x + 15) = -30x - 75 \]
-
Substitute this back into the equation: \[ 20x - 30x - 75 = -45 \]
-
Combine like terms: \[ -10x - 75 = -45 \]
-
Add \(75\) to both sides: \[ -10x = -45 + 75 \] \[ -10x = 30 \]
-
Divide both sides by \(-10\): \[ x = \frac{30}{-10} = -3 \]
This means \( x = -3 \).
However, let's look at the answer choices provided:
- \(0x = -3\)
- \(x = 3\)
- \(0x = 2\)
- \(x = -2\)
Since \(-3\) is not listed as an option, I will recheck my calculations.
Let's redo the calculations briefly again:
The equation starts with: \[ 20x - 5(6x + 15) = -45 \] Distributing: \[ 20x - 30x - 75 = -45 \] Simplifying: \[ -10x - 75 = -45 \] \[-10x = 30\] Dividing: \[ x = -3 \]
The calculations are confirmed. However, none of the provided options match \(x = -3\). Please double-check the original problem or answer choices provided.